2008
DOI: 10.1007/s10964-008-9352-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Responses to Racial Rejection Images Among Young Adults from African-American Backgrounds

Abstract: Physiologic reactivity to racially rejecting images was assessed in 35 young adults (10 males, 25 female) from African-American backgrounds using the startle probe paradigm. In a laboratory setting, participants viewed 16 images depicting racial rejection, racial acceptance, nonracial negative, and nonracial positive themes. While viewing these images, startling bursts of noise were presented and the magnitude of the eyeblink responses were measured. Results supported an attentional mechanism which suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Still, the compiled evidence does build some theoretical support for an interactive effect of race/ethnicity and gender on stress response and management style [64,83,181,184,201,203,207,209]. Particularly among black women and men, race and gender identities as unique cultural scripts and adaptive processes are thought to feature prominently in their distinctive reactions to social identity stressors [64,131,141,142,203].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Still, the compiled evidence does build some theoretical support for an interactive effect of race/ethnicity and gender on stress response and management style [64,83,181,184,201,203,207,209]. Particularly among black women and men, race and gender identities as unique cultural scripts and adaptive processes are thought to feature prominently in their distinctive reactions to social identity stressors [64,131,141,142,203].…”
Section: Discussionmentioning
confidence: 97%
“…Cultural context-In 17 of the 45 studies empirically confirming theory, evidence suggested that the diversity in stress management strategies across racial/ethnic groups results more from the distinct cultural contexts in which these groups are situated. The centrality and content of racial/ethnic identity [33,58,59,74,79,82,106,[140][141][142][143][144][145][146][147][148], personal or familial beliefs about race [105,134,135,148,149], and dominant racial narratives [40,79,108,148,150] are theorized as some of the primary contributors to coping preferences and are framed as products of culturally-indoctrinated principles and practices.…”
Section: Theories For Racial/ethnic Variation In Stress Response and mentioning
confidence: 99%
“…Their findings suggested that variability in gender rejection sensitivity within women can predict a variety of engagement outcomes, including feelings of self-doubt, perceptions of sexism, self-silencing, and alienation within the context of a competitive, maledominated law school culture. A study of undergraduates of African American backgrounds found that those who felt more positively about their racial group appeared less affected by racial rejection (Kiang, Blumenthal, Carlson, Lawson, & Shell, 2009). Page-Gould, Mendoza-Denton, and Mendes (2014) found that racebased rejection sensitivity was related to greater stress symptoms among Black adults who reported fewer cross-race friends but not among participants who had more cross-race friends.…”
Section: Sensitivity To Status-based Rejectionmentioning
confidence: 99%
“…Although existing work is mixed, we expected that, in line with research on emotional expression and recovery from negative events (Frattaroli, 2006; Holmes et al, 2007), higher psychological well-being would be associated with the greater use of negative emotion words when describing discrimination incidents. Our rationale stems from the idea that discrimination is inherently stressful on multiple levels (Kiang, Blumenthal, Carlson, Lawson, & Shell, 2009); hence, some negative emotionality should be normatively expected. Some work has also shown that suppressing negative emotions in the context of an upsetting event can contribute to stress and anxiety (Gross, 2002).…”
Section: The Present Study: Exploring Linguistic Characteristics In D...mentioning
confidence: 99%